Topologies comparison and rotor optimization of the hybrid axial transverse flux permanent magnet motor - Pengcheng Ma; Yong Li; Qian Wang; Jianhui Hu (Energy Reports, 2022)
With the advantages of high power density, the hybrid axial transverse flux permanent magnet motor (HATF-PMM) is investigated in this paper. Eight topologies of the novel HATF-PMM are proposed, analysed and compared. The applicable scopes of different topologies are summarized and the optimal topology is selected. Based on the characteristics of hybrid flux motor, an indirect optimization method through magnetic circuit decoupling and recombination is proposed. The rotor parameter optimization is performed by the proposed indirect optimization method. In the end, the HATF-PMM scheme with high power density is obtained, and the optimization law of HATF-PMM rotor parameters is revealed through the optimization process, which proves that the HATF-PMM has great potential in the application of more-electric aircraft.